الإستقطاب في دعوة النبي صلى الله عليه وسلم المحاور التجميعية أنموذجا - بيكي, رميصاء (جامعة الوادي university of eloued, 2017)
تلقي ىذه ابؼذكرة الضوء على الاستقطاب في دعوة النبِ صلى ا﵁ عليو ك سلم من خلاؿ معرفة الوسائل التي استعملها رجل الدعوة الأكؿ في دعوتو الى ا﵁ تعالى، كالتي بسثلت في استقطابو )عليو الصلاة كالسلا( عن طريق الدعاء بابؽداية إلى ا﵁ عز كجل، كمن كسائلو كذلك تأليف القلوب بنوعيو ابؼعنوم ك ابؼادم: فأما ابؼعنوم فوظف فيو عليو )الصلاة كالسلا (كلا من ابؼدح كالثناء كالعفو، كأما ابؼادم فقد بسحور على عطائو كجوده )صلى ا﵁ عليو كسلم(، لكل من الأفراد كابعماعات، كأبى الاستقطاب بلقائو الشخصي صلى ا﵁ عليو كسلم في الأسواؽ كابؼواسم إلا أف يبلغ الذركة كالسنا في الدعوة إلى ا﵁ )عز كجل(، كاستطاع بهذه الوسيلة أف يغتَ بؾرل التاريخ، كثقة الرسوؿ )صلى ا﵁ عليو كسلم( في الصحابة ظاىرة ،كيف لا كىو الذم بعث ىؤلاء الثقات كىم: مصعب بن عمتَ، كمعاذ بن جبل، كأبو موسى الأشعرم، كخالد بن الوليد رضي ا﵁ عنهم في ترغيب الناس للدخوؿ في الإسلا، كما أف صدل الإسلا لم يتوقف على ىاتو الوسائل التي ذكرناىا آنفا فحسب، كإبما أتت كسيلة الرسالة ابؼكتوبة التي خطها بيده الشريفة، مؤدية دكرىا كذلك فكاف ىذا ختا رسالتي.This study sheds light on Prophet Mohammed’s strategy of “attraction” in his call to Islam. He mainly used two techniques within this strategy: supplication for guidance and linking hearts together materially and psychologically. Within joining hearts psychologically، he used praise، laudation and forgiveness; as for material option، he used to grant money to individuals and communities alike. However، Mohammed’s attraction strategy reached its peak in popular markets and religious seasons. This enabled him to change history with the help of his companions، such as Musaab Ibn Umair، Muadh Ib Jabal، Abou Musa Al Ashari، Khaled Ibn Walid، etc.، whom he sent to all regions to ask people to convert to Islam. Another strategy which can be added to all what has been said is that of hand-written messages which managed to convince many people to adopt Islam as their religion. This had a great impact on the spread of Islam all over the world.
مذكرة
Keywords: الإستقطاب/دعوة/المحاور; polarizing/inviting/interlocutors